2005
DOI: 10.1167/iovs.04-0245
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Bioluminescent Imaging of Human Uveal Melanoma in a New Mouse Model of Local Tumor Growth and Metastasis

Abstract: BLI enables continuous quantitative monitoring in the same animal of growth kinetics for each tumor and its metastases. This model will accelerate the understanding of the pathogenesis and treatment of uveal melanoma and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Other studies have shown hepatic, bone, and visceral micrometastasis develop in a uveal melanoma xenograft model (34), as well as bone and visceral macrometastasis in an intracardiac metastatic mouse model (35). Another study has also demonstrated inhibition of micrometastasis using a VEGFR inhibitor after enucleation of the mouse eyes (36).…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have shown hepatic, bone, and visceral micrometastasis develop in a uveal melanoma xenograft model (34), as well as bone and visceral macrometastasis in an intracardiac metastatic mouse model (35). Another study has also demonstrated inhibition of micrometastasis using a VEGFR inhibitor after enucleation of the mouse eyes (36).…”
Section: Discussionmentioning
confidence: 96%
“…Stable cell lines were generated by using the Flp-In system (Invitrogen, Breda, The Netherlands) according to manufacturer's protocol and as described previously (Notting et al, 2005). In short, an MDA-MB-231-Flp-in host cell line (MDA-MB-231-Frt3) was generated by a stable introduction of a single copy of an Flp-Recombinase target (FRT) site as an integral part of an antibiotic resistance gene (blasticidin) in the genome of these cells (5 mg/ml blasticidin was added to the culture medium).…”
Section: Generation Of Isogenic Cell Lines By Targeted Integrationmentioning
confidence: 99%
“…31) were selected to generate a stable cell line that overexpresses BMP7. Stable cell lines were generated using the Flp-In system (Invitrogen) according to the manufacturer's protocol (32). In short, a MDA-231-BO2-Flp-in host cell line (MDA-231-BO2-Frt11) was generated by stable introduction of a single copy of a Flp recombinase target (FRT) site as an integral part of an antibiotic resistancy gene in the genome of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to Flp-mediated recombination at the genomic FRT site, this targeting vector was incorporated in the genome. Simultaneously, a shift in antibiotic resistance was introduced allowing positive selection for integrants in the genomic FRT site only and negative selection for random integrants in one single step (32). This method allows the generation of isogenic stable cell lines, which only differ in sequence inserted in the genomic FRT site, thereby eliminating the need for clonal selection.…”
Section: Introductionmentioning
confidence: 99%